2018
DOI: 10.1515/cclm-2017-0870
|View full text |Cite
|
Sign up to set email alerts
|

Telomere biology and age-related diseases

Abstract: Telomeres are the protective end caps of chromosomes and shorten with every cell division. Telomere length has been proposed as a biomarker of biological age and a risk factor for age-related diseases. Epidemiologic studies show an association between leukocyte telomere length (LTL) and mortality. There is solid evidence that links LTL with cardiovascular disease. Short telomeres promote atherosclerosis and impair the repair of vascular lesions. Alzheimer's disease patients have also a reduced LTL. Telomeres m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
147
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(154 citation statements)
references
References 92 publications
3
147
0
4
Order By: Relevance
“…Prospective observational studies in healthy and high-risk populations have shown that short telomeres substantially increase the risk of all-cause and cardiovascular (CVD) mortality [8][9][10]. Environmental and lifestyle factors, such as exposure to UV radiation, smoking, stress, obesity, diet, and lack of physical activity, can modify the velocity of telomere shortening [2,11]. Many of these factors are associated with increased oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Prospective observational studies in healthy and high-risk populations have shown that short telomeres substantially increase the risk of all-cause and cardiovascular (CVD) mortality [8][9][10]. Environmental and lifestyle factors, such as exposure to UV radiation, smoking, stress, obesity, diet, and lack of physical activity, can modify the velocity of telomere shortening [2,11]. Many of these factors are associated with increased oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44][45] As so, TL is also another widely discussed biomarker since it has been widely associated with innumerous diseases, environmental exposures and phenotypic characteristics. 10,40,46 There are several methods to determine the TL in tissues, single cells and DNA preparations. 47 For several years, the golden standard in the determination of the TL was the analysis of the terminal restriction fragment (TelRF) by Southern blot.…”
Section: Telomeres As Biomarkers In Cancermentioning
confidence: 99%
“…At each round of DNA replication, part of telomeres is successively lost, resulting in telomere shortening [5]. Reduced telomere length is associated with cellular aging [6], genetic diseases [7,8], cancers, and chronic diseases [9,10]. Measuring telomere length is, therefore, considered as an attractive biomarker for potential risk stratification in various diseases.…”
Section: Introductionmentioning
confidence: 99%